Multi-output AC-AC converter for domestic induction heating - Ozturk, Metin; Altintas, Nihan (SPRINGER, 2023)
In this study, a new multi-output direct AC-AC converter is proposed. The proposed new converter consists of a combination of half-bridge (HB) and single-switch quasi-resonant (QR) topologies. In the proposed converter, the number of coils can be increased, all coils can be controlled independently, and independent power control can be made. The main problem of multi-output induction heating systems, such as the inability to increase the number of loads and to control the coils independently, has been eliminated with the proposed converter. The control of the converter is easy, cheap, and simple. The theoretical analysis of the proposed circuit is verified experimentally. In simulation and experimental studies, three coils were used at the output of the converter and each coil is designed to transfer 2000 W of power to the output. The proposed converter has been compared in detail with the conventional direct AC-AC converter in the same conditions. The new converter improves the performance and efficiency of induction heating systems.
Keywords: AC-AC conversion; Domestic induction heating; Half-bridge converters; Induction cookers; Multi-output systems; Single-switch converters; SERIES-RESONANT INVERTER; DESIGN; IMPLEMENTATION; Engineering